Qanun Aceh No.6 Tahun 2014 Tentang Hukum Jinayat Menurut Perspektif Moderasi Beragama - Danial, Danial (Syarah: Jurnal Hukum Islam dan Ekonomi, 2023)
Qanun Jinayat is one of the legal umbrellas for implementing Islamic law in the Criminal sector in Aceh. The application of this Qanun has pros and cons because it is seen as contrary to the spirit of tolerance which is one of the pillars of Religious Moderation. This study examines the suitability of the Jinayat Qanun with Religious Moderation. The data used in this article consists of primary data and secondary data. Primary data comes from Qanun Aceh No. 6 of 2014 concerning Jinayat Law. Meanwhile, secondary data was obtained from literature related to the implementation of Islamic law in Aceh and articles related to religious moderation. The study results show that Qanun Jinayat is following Religious Moderation for the first two reasons that this Qanun in its formulation chooses the Minhaji approach, not the Mazhabi approach. Second, non-Muslims are given a choice in their implementation to choose to submit to the punishment in the Qanun Jinayat or the penalties contained in the Indonesian Criminal Code if they violate the Qanun Jinayat in the Aceh region.